Answer:
f(x) = x⁴-6x³-13x²+66x+72
Step-by-step explanation:
Factors are: (x+3)(x+1)(x-4)(x-6)
[(x+3)(x+1)][(x-4)(x-6)]
[x²+3x+x+3][x²-4x-6x+24]
(x²+4x+3)(x²-10x+24)
x⁴+4x³+3x²-10x³-40x²-30x+24x²+96x+72
f(x) = x⁴-6x³-13x²+66x+72
Answer:
3x
Step-by-step explanation:
![\frac{d}{dx} (3x {}^{2} )](https://tex.z-dn.net/?f=%20%5Cfrac%7Bd%7D%7Bdx%7D%20%283x%20%20%7B%7D%5E%7B2%7D%20%29)
![\frac{1}{x} 3 {x}^{2}](https://tex.z-dn.net/?f=%20%5Cfrac%7B1%7D%7Bx%7D%203%20%7Bx%7D%5E%7B2%7D%20)
![3x](https://tex.z-dn.net/?f=3x)
C or d i think is the correct answer
The equation will be 2x + 7 = 3x
subtract 2x from bothsides, you get 7 = x
so x is equal to 7
EDITED
sorry, i didnt read the sum part, so my answer is considered wrong ahaha
2(x+7) equals 3x
distribute, you get 2x+14=3x
then subtract 2x,
the answer for x is 14
The bicycle costs $30 and Hugo finishes paying after 15 weeks. When he has paid for the bike, y=0 because he owes nothing. So -10=-2x+20, 2x=30, x=15. And the cost of the bike is 2×15=$30.